Mosaic tissue distribution of the tandem duplication of LAMP2 exons 4 and 5 demonstrates the limits of Danon disease cellular and molecular diagnostics. Issue 1 (29th May 2013) - Majer, Filip; Pelak, Ondrej; Kalina, Tomas; Vlaskova, Hana; Dvorakova, Lenka; Honzik, Tomas; Palecek, Tomas; Kuchynka, Petr; Masek, Martin; Zeman, Jiri; Elleder, Milan; Sikora, Jakub
Abstract : Abstract: Alu‐ mediated tandem duplication of exons 4 and 5 (g.15815_22218dup6404) is a novel mutation that has been detected in the LAMP2 gene ( Xq24 ). This exon copy number variation was found in two brothers with the typical phenotype of Danon disease, including characteristic myocardial changes on magnetic resonance imaging. The 6.4 kb duplication was identified in both boys by a combination of exon dosage qPCR analyses and duplication breakpoint/junction mapping. The rearrangement results in a plethora of abnormal LAMP2 splicing variants and also in use of likely cryptic splice sites in the 3′ terminus of LAMP2 gene. Although we found minute amounts of normal LAMP2B and LAMP2A mRNAs, no protein was detectable in peripheral blood leukocytes by flow cytometry in both brothers. Uniquely, the fraction of LAMP2‐deficient granulocytes (0.06 %) assessed by flow cytometry in the patients' asymptomatic mother substantially differed from the random distribution of X‐chromosome inactivation in her leukocytes. This discrepancy was later explained by molecular genetic methods as a consequence of mosaic distribution of the mutation in her somatic tissues. Altogether, we report a novel and mosaically distributed exon copy number rearrangement in the LAMP2 gene and comment on obstacles this genetic setup presents to the overall cellular and molecular diagnostic algorithm of Danon disease. Our observations of the mosaicism in the asymptomatic mother suggest that similarly affected females could be a potentially under‐diagnosed Danon disease carrier group and that LAMP2 flow cytometry, because of its supreme sensitivity, can be an efficient method for pedigree screening.